Disproportionation of ethylbenzene over SAPO-40 - Lourenço, J. P. (1996)
SAPO-40 exhibits strong acid sites, which catalyse the reaction of disproportionation of ethylbenzene. The distribution of diethylbenzene isomers suggests a high void volume in the structure of this molecular sieve.